Konsep Dualistis dalam Pertunjukan Gender Wayang pada Pekan Seni Remaja Kota Denpasar Tahun 2015 - Ni Putu Hartini (Institut Seni Indonesia Denpasar, 2021)
Purpose: This paper discusses Gender Wayang, which is one of the older Balinese gamelan types. The progress that has occurred is that the public's interest in the Gender Wayang instrument is growing due to the orientation of the function which prioritizes as a form of performance that has aesthetic elements. Research methods: Qualitative research methods are carried out by relying on field data, applied to primary and secondary data sources where the data collected is carried out through direct interviews with creators or artists. Results and discussion: One form of this performance is at Pekan Seni Remaja Denpasar (Denpasar Youth Art Week), which is presented by a group of SMPN 6 Denpasar musicians. This is interesting as well as a challenge to examine the problem of how the Dualistic Concept in the Gender Wayang Performance at the Denpasar Youth Art Week 2015. The dualistic concept in the Gender Wayang performance at the Denpasar Youth Art Week 2015 can be seen from every element in the Gender Wayang performance. Implication: This dualistic concept can be viewed from the form of the instrument or the Gamelan Gender Wayang itself and its presentation system.